2008
DOI: 10.1186/1471-2164-9-458
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline modulates the global transcriptional profile of Salmonella revealing a role in the antimicrobial peptide and oxidative stress resistance responses

Abstract: Background: The successful interaction of bacterial pathogens with host tissues requires the sensing of specific chemical and physical cues. The human gut contains a huge number of neurons involved in the secretion and sensing of a class of neuroendocrine hormones called catecholamines. Recently, in Escherichia coli O157:H7, the catecholamines adrenaline and noradrenaline were shown to act synergistically with a bacterial quorum sensing molecule, autoinducer 3 (AI-3), to affect bacterial virulence and motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 77 publications
4
89
0
Order By: Relevance
“…Recently, we have shown that epinephrine increases sensitivity to polymyxin B in a manner dependent on the twocomponent system BasSR (36). We saw no change in expression of virK or mig14 in the ⌬basS mutant compared to the wild type, either with or without epinephrine/norepinephrine (data not shown), suggesting that virK and mig14 are regulated by epinephrine/norepinephrine through a mechanism independent of BasSR.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…Recently, we have shown that epinephrine increases sensitivity to polymyxin B in a manner dependent on the twocomponent system BasSR (36). We saw no change in expression of virK or mig14 in the ⌬basS mutant compared to the wild type, either with or without epinephrine/norepinephrine (data not shown), suggesting that virK and mig14 are regulated by epinephrine/norepinephrine through a mechanism independent of BasSR.…”
Section: Resultsmentioning
confidence: 61%
“…Epinephrine has been shown to decrease resistance to polymyxin B through downregulation of the pmr operon, in a man- ner dependent on the two-component system BasSR (36). We have shown that expression of virK and mig14 is independent of BasSR, suggesting that stress hormones affect LL-37 and polymyxin B resistance by two independent mechanisms.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations